An Evaluation of Knowledge, Attitude and Practice of Adverse Drug Reaction Reporting in Dental Practice - Talattof, Zahra; Azad, Azita (Pakistan Journal of Nutrition, 2015)
While adverse drug reaction (ADR) reporting card (yellow card) system has started in 1998 in Iran, the ADR reporting rate was very low. To explore if the Iranian adverse drug reaction reporting system could be modified and to determine causes of under-reporting among dentists, a study to investigate the role of dentists in ADR reporting was done in marvdasht city (Fars province, south of Iran). A cross-sectional study was done between February and December 2014 in marvdasht city, Iran. After describing the study and its aims for each dentist, oral consent was taken. A number of 40 out of 50 dentists (80%) agreed to participate in the interview. All respondents were working in private dental clinic. Although level of knowledge regarding ADR was low among dentists, all of them admitted that paying attention to ADRs and timely reporting is very important. About ADR in the university, 10% believed that it was enough, 70% claimed that it was not satisfactory and 20% admitted that it was little. It is concluded that Our dentists have little knowledge about the process, goal and importance of ADR reporting system. Otherwise, education and training will be important in maintaining and enhancing ADR reports by dentists.